Preparation method of hard carbon material and application of hard carbon material in sodium-ion battery

Through carboxyl-induced Diels-Alder reaction and carbon shell coating technology, the sodium storage specific capacity and initial Coulomb efficiency of the sodium ion battery negative electrode material are improved, and the problems of high cost and insufficient performance in the existing technology are solved, thereby achieving efficient and reliable preparation of the sodium ion battery negative electrode material.

CN119551655AActive Publication Date: 2025-03-04DALIAN UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411736316.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The high cost of existing sodium ion battery negative electrode materials, insufficient sodium storage capacity and initial Coulomb efficiency, limit the commercialization and large-scale application of sodium ion batteries.

Method used

The crosslinking degree of soft carbon precursors is enhanced through the carboxyl-induced Diels-Alder reaction, prevents the rearrangement of graphite microcrystalline fragments, forms a turbine-type structural hardcarbon material, and reduces the surface defects of the hardcarbon material through the carbon shell coating.

Benefits of technology

The reversible sodium storage specific capacity and initial Coulomb efficiency of hard carbon materials are significantly improved, and the high added value utilization of soft carbon precursors is achieved, which is suitable for the commercial preparation of sodium ion battery negative electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551655A_ABST
    Figure CN119551655A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a hard carbon material and application of the hard carbon material in a sodium-ion battery. The preparation method comprises the following steps: uniformly mixing soft carbon precursor powder with carboxylic acid dienophile, carrying out Diels-Alder reaction in a reaction kettle to obtain a carboxylated soft carbon precursor, and carrying out high-temperature carbonization to obtain the hard carbon material. The thermal conversion process of the soft carbon precursor is adjusted and the crosslinking degree of the soft carbon precursor is enhanced by introducing carboxyl, so that rearrangement of adjacent graphite microcrystal fragments is effectively prevented, and the hard carbon material with rich closed-cell structures and expanded interlayer spacing is formed; in addition, the surface of the hard carbon material is coated with a carbon shell, so that surface defects of the hard carbon material are effectively reduced. The obtained hard carbon material is used as a sodium-ion battery negative electrode, shows excellent reversible sodium storage specific capacity and initial coulombic efficiency, and realizes high value-added utilization of petroleum coke. The carbon precursor adopted by the method is wide in source, low in cost and easy to obtain, the preparation process is simple, convenient, safe and reliable, the cost is controllable, and the method is suitable for large-scale production and practical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical energy storage, and specifically relates to a preparation method of a hard carbon material and its application in sodium ion batteries. Background Art

[0002] The availability of key resources and the growing demand for large-scale energy storage devices have once again made research on sodium-ion batteries a focus. The commercialization of sodium-ion batteries depends largely on the innovation of low-cost and high-performance electrode materials. The graphite anode commonly used in lithium-ion batteries does not have sodium storage activity electrochemically, so the anode material has become the main bottleneck in the development of sodium-ion batteries. At present, research on sodium-ion battery anodes mainly focuses on hard carbon materials, and some progress has been made. However, the reported hard carbon precursors, such as biomass, resins, and polymers, generally face problems of high cost and low yield, which affect the overall cost-effectiveness of sodium-ion batteries. Based on this, exploring low-cost precursors or optimizing the preparation process is crucial to promote the large-scale application of sodium-ion batteries.

[0003] Soft carbon precursors, such as petroleum coke, coal, and asphalt, are considered ideal candidates for electrode material precursors in large-scale energy storage equipment due to their low cost, high carbon content, and good conductivity. However, during the carbonization process, soft carbon precursors tend to form highly graphitized structures. The low interlayer spacing and regular structure are not conducive to the effective embedding of sodium ions between the layers, nor are they conducive to the adsorption of sodium ions on defect sites. Therefore, they exhibit low reversible sodium storage capacity and initial Coulombic efficiency. In order to overcome these challenges, researchers have explored a variety of modification strategies. A Chinese invention patent (publication number: CN118083943A) introduces a method of activating petroleum coke with KOH and then mixing it with asphalt for secondary high-temperature carbonization to prepare a porous core-shell structured sodium ion battery negative electrode carbon material. Although this method can improve the sodium storage performance to a certain extent, the improvement is limited, reaching only about 250mAh g -1 Another patent (publication number: CN118289731A) proposes to use mixed acid to treat petroleum coke to prepare a coating carbon material, which is used for hard carbon surface coating to reduce the pores and defects on the surface of the hard carbon material, thereby increasing the initial Coulomb efficiency and reversible specific capacity to 64.9% and 223.6 mAh g -1. At present, the sodium storage capacity of soft carbon precursor-derived carbon is mainly improved by acid oxidation, strong alkali activation and high-temperature carbonization. Although these methods have improved the sodium storage performance to a certain extent, they are still insufficient to meet the requirements of practical applications, and there are problems such as complex operation, environmental pollution, safety and commercialization difficulties in the processing process. In view of the above situation, it is urgent to develop a new type of sodium ion battery negative electrode material that is environmentally friendly, low-cost, and can significantly improve the sodium storage capacity and initial coulombic efficiency, so as to meet the needs of future large-scale energy storage systems for efficient and reliable sodium ion batteries. Summary of the invention

[0004] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a method for preparing a hard carbon material and its application in sodium ion batteries. The present invention provides a low-cost, simple, safe and reliable preparation method, which improves the crosslinking degree of the soft carbon precursor by carboxyl induction, effectively prevents the rearrangement of adjacent graphite crystallite fragments inside the soft carbon precursor, and realizes the transformation of the soft carbon precursor-derived carbon from highly graphitized soft carbon to turbine-type structured hard carbon. The suitable carbon layer spacing and closed-pore structure inside the hard carbon provide a large number of effective storage sites for sodium ions; in addition, the surface of the hard carbon material is coated with a carbon shell, which effectively reduces the surface defects of the hard carbon material and significantly improves its initial coulombic efficiency; the obtained hard carbon material exhibits excellent reversible sodium storage specific capacity and initial coulombic efficiency, realizing the high added value utilization of the soft carbon precursor.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing a hard carbon material comprises the following steps:

[0007] (1) uniformly mixing soft carbon precursor powder and carboxylic acid dienophile, and performing Diels-Alder reaction in a reactor to obtain a carboxylated soft carbon precursor;

[0008] (2) The carboxylated soft carbon precursor is carbonized at high temperature to obtain a hard carbon material.

[0009] The soft carbon precursor includes one or more of petroleum coke, asphalt and coal.

[0010] The petroleum coke is one or more of low-sulfur petroleum coke, medium-sulfur petroleum coke and high-sulfur petroleum coke; the asphalt includes one or more of low-temperature asphalt, medium-temperature asphalt and high-temperature asphalt; the coal includes one or more of bituminous coal, anthracite and lignite.

[0011] Step (1) also includes pre-treating the soft carbon precursor powder by ball milling before the soft carbon precursor powder and the carboxylic acid dienophile are uniformly mixed.

[0012] The ball milling speed is 400-1000 rpm, and the ball milling time is 0.1-4 h.

[0013] The carboxylic acid dienophile includes one or more of maleic acid, maleic anhydride, acrylic acid and acetylene dicarboxylic acid.

[0014] The mass ratio of the soft carbon precursor to the carboxylic acid dienophile is 1:(1-20).

[0015] The Diels-Alder reaction is carried out in a closed reactor at a reaction temperature of 150-240° C. and a reaction time of 1-15 h.

[0016] Step (1) further comprises washing and drying the carboxylated soft carbon precursor. Further, the washing solvent comprises one or more of water, acetone, tetrahydrofuran, benzene and chloroform.

[0017] The temperature of the high-temperature carbonization is 800-1600° C., and the time of the high-temperature carbonization is 0.5-5 h.

[0018] The high-temperature carbonization process is carried out in an inert atmosphere.

[0019] The heating rate of high temperature carbonization is 1-10℃ / min.

[0020] The present invention also provides an application of the hard carbon material in a sodium ion battery, wherein the hard carbon material is used as a negative electrode of the sodium ion battery.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] 1. The present invention provides a low-cost, safe and reliable method for preparing hard carbon materials. The method creatively changes the conventional path of directly carbonizing a traditional soft carbon precursor to form a highly graphitized soft carbon. The crosslinking degree of the soft carbon precursor is improved by carboxyl induction, which effectively prevents the rearrangement of adjacent graphite crystallite fragments inside the soft carbon precursor, and realizes the transformation of the soft carbon precursor-derived carbon from highly graphitized soft carbon to turbine-type structured hard carbon. The suitable carbon layer spacing and closed-pore structure inside the hard carbon provide a large number of effective storage sites for sodium ions, showing an excellent reversible sodium storage capacity, and realizing the high added value utilization of the soft carbon precursor.

[0023] 2. The carboxylic acid dienophile used in the present invention can form a carbon shell in situ during the subsequent carbonization process, which is coated on the surface of the hard carbon, effectively reducing the surface defects of the hard carbon material and significantly improving its initial coulombic efficiency.

[0024] 3. The preparation method described in the present invention has simple process, green and environmental protection, low cost, is suitable for large-scale production and practical application, and is of great significance to the future commercial preparation of sodium ion battery negative electrode.

[0025] 4. The hard carbon material prepared by the preparation method provided by the present invention is used as the negative electrode material of sodium ion battery, and the reversible specific capacity is as high as 326.3 mAh g -1 , the initial Coulombic efficiency is as high as 90%. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 These are infrared spectra of petroleum coke and carboxylated petroleum coke precursor.

[0027] Figure 2 This is the XRD image of the petroleum coke-based hard carbon material prepared in Example 1.

[0028] Figure 3 This is a TEM image of the petroleum coke-based hard carbon material prepared in Example 1.

[0029] Figure 4 This is a constant current charge and discharge curve diagram of the first cycle charge and discharge process of the petroleum coke-based hard carbon material prepared in Example 1.

[0030] Figure 5 This is a constant current charge and discharge curve diagram of the petroleum coke-based hard carbon material prepared in Example 2 during the first cycle of charge and discharge.

[0031] Figure 6 This is a constant current charge and discharge curve diagram of the petroleum coke-based hard carbon material prepared in Example 3 during the first cycle of charge and discharge.

[0032] Figure 7 This is a constant current charge and discharge curve diagram of the petroleum coke-based hard carbon material prepared in Example 4 during the first cycle of charge and discharge.

[0033] Figure 8 This is a constant current charge and discharge curve diagram of the petroleum coke-based hard carbon material prepared in Example 5 during the first cycle of charge and discharge.

[0034] Fig. 9 This is a constant current charge and discharge curve diagram of the petroleum coke-based hard carbon material prepared in Example 6 during the first cycle of charge and discharge.

[0035] Fig.10 This is the XRD image of the petroleum coke-based soft carbon material prepared in Comparative Example 1.

[0036] Fig.11 This is a TEM image of the petroleum coke-based soft carbon material prepared in Comparative Example 1.

[0037] Fig.12 This is a constant current charge and discharge curve diagram of the first cycle charge and discharge process of the petroleum coke-based soft carbon material prepared in Example 1.

[0038] Fig.13 This is the XRD image of the petroleum coke-based hard carbon material prepared in Comparative Example 2.

[0039] Fig.14 This is a constant current charge and discharge curve diagram of the first cycle charge and discharge process of the petroleum coke-based hard carbon material prepared in Example 2.

[0040] Fig.15 This is a constant current charge and discharge curve diagram of the first cycle charge and discharge process of the petroleum coke-based soft carbon material prepared in Example 3. DETAILED DESCRIPTION

[0041] The present invention is described in detail below through some representative embodiments, but the present invention is not limited to these embodiments.

[0042] Example 1

[0043] This embodiment provides a method for preparing a petroleum coke-based hard carbon material, and the specific operation steps are as follows:

[0044] 3g of high-sulfur petroleum coke powder was ball-milled at 800rpm for 1h to obtain ball-milled petroleum coke. 3g of the ball-milled petroleum coke obtained above was ground and mixed with 9g of maleic anhydride, and then placed in a closed reactor for Diels-Alder reaction at a reaction temperature of 220°C and a reaction time of 8h. After the reaction was completed, it was naturally cooled to room temperature, washed with tetrahydrofuran to remove unreacted maleic anhydride, and dried in a vacuum oven at 50°C for 12h to obtain a carboxylated petroleum coke precursor. Figure 1 The infrared spectra of petroleum coke and carboxylated petroleum coke precursor show that the Diels-Alder reaction can precisely graft a large number of carboxyl groups on the surface of petroleum coke. 1g of carboxylated petroleum coke precursor was placed in a tubular carbonization furnace, heated to 1500℃ at a heating rate of 3℃ / min under an argon atmosphere, and maintained at this temperature for 2h, then cooled to 1000℃ at a cooling rate of 2℃ / min, and then naturally cooled to room temperature to obtain a hard carbon material. Figure 2 This is the XRD diagram of the hard carbon material prepared in this example. It can be seen that the material exhibits an amorphous structural feature, and the carbon layer spacing calculated according to the Bragg formula is 0.365 nm. Figure 3 TEM image of the hard carbon material prepared in this example. The material exhibits turbine-type structural characteristics with rich closed pores and extended interlayer spacing, and is mainly composed of a graphite-like phase and a pseudographite phase.

[0045] Example 2

[0046] This embodiment provides a method for preparing a petroleum coke-based hard carbon material, and the specific operation steps are as follows:

[0047] Take 3g of high-sulfur petroleum coke powder and ball-mill it at 800rpm for 2h to obtain ball-milled petroleum coke. Grind and mix 3g of the above-obtained ball-milled petroleum coke with 9g of maleic anhydride, and then place it in a closed reactor for Diels-Alder reaction at a reaction temperature of 220℃ and a reaction time of 8h. After the reaction is completed, it is naturally cooled to room temperature, and the unreacted maleic anhydride is removed by washing with tetrahydrofuran, and dried at 50℃ in a vacuum oven for 12h to obtain a carboxylated petroleum coke precursor. Place 1g of carboxylated petroleum coke precursor in a tubular carbonization furnace, and in an argon atmosphere, heat it to 1500℃ at a heating rate of 3℃ / min, and keep it at this temperature for 2h, then cool it to 1000℃ at a cooling rate of 2℃ / min, and then cool it naturally to room temperature to obtain a hard carbon material.

[0048] Example 3

[0049] This embodiment provides a method for preparing a petroleum coke-based hard carbon material, and the specific operation steps are as follows:

[0050] Take 3g of high-sulfur petroleum coke powder and 9g of maleic anhydride, grind and mix them evenly, and then place them in a closed reactor for Diels-Alder reaction, the reaction temperature is 220℃, and the reaction time is 8h. After the reaction is completed, it is naturally cooled to room temperature, and the unreacted maleic anhydride is removed by washing with tetrahydrofuran, and dried at 50℃ in a vacuum oven for 12h to obtain a carboxylated petroleum coke precursor. 1g of carboxylated petroleum coke precursor is placed in a tubular carbonization furnace, and in an argon atmosphere, the temperature is increased to 1500℃ at a heating rate of 3℃ / min, and maintained at this temperature for 2h, and then cooled to 1000℃ at a cooling rate of 2℃ / min, and then naturally cooled to room temperature to obtain a hard carbon material.

[0051] Example 4

[0052] This embodiment provides a method for preparing a petroleum coke-based hard carbon material, and the specific operation steps are as follows:

[0053] Take 3g of high-sulfur petroleum coke powder and ball-mill it at 800rpm for 1h to obtain ball-milled petroleum coke. Grind and mix 3g of the above-obtained ball-milled petroleum coke with 3g of maleic anhydride, and then place it in a closed reactor for Diels-Alder reaction at a reaction temperature of 220℃ and a reaction time of 8h. After the reaction is completed, it is naturally cooled to room temperature, and the unreacted maleic anhydride is removed by washing with tetrahydrofuran, and dried at 50℃ in a vacuum oven for 12h to obtain a carboxylated petroleum coke precursor. Place 1g of carboxylated petroleum coke precursor in a tubular carbonization furnace, and in an argon atmosphere, heat it to 1500℃ at a heating rate of 3℃ / min, and keep it at this temperature for 2h, then cool it to 1000℃ at a cooling rate of 2℃ / min, and then cool it naturally to room temperature to obtain a hard carbon material.

[0054] Example 5

[0055] This embodiment provides a method for preparing a petroleum coke-based hard carbon material, and the specific operation steps are as follows:

[0056] Take 3g of high-sulfur petroleum coke powder and ball-mill it at 800rpm for 1h to obtain ball-milled petroleum coke. Grind and mix 3g of the above-obtained ball-milled petroleum coke with 9g of acrylic acid, and then place it in a closed reactor for Diels-Alder reaction at a reaction temperature of 220℃ and a reaction time of 8h. After the reaction is completed, it is naturally cooled to room temperature, washed with water to remove unreacted acrylic acid, and dried at 50℃ in a vacuum oven for 12h to obtain a carboxylated petroleum coke precursor. Place 1g of carboxylated petroleum coke precursor in a tubular carbonization furnace, and in an argon atmosphere, heat it to 1500℃ at a heating rate of 3℃ / min, and keep it at this temperature for 2h, then cool it to 1000℃ at a cooling rate of 2℃ / min, and then naturally cool it to room temperature to obtain a hard carbon material.

[0057] Example 6

[0058] This embodiment provides a method for preparing a petroleum coke-based hard carbon material, and the specific operation steps are as follows:

[0059] Take 3g of high-sulfur petroleum coke powder and ball-mill it at 800rpm for 2h to obtain ball-milled petroleum coke. Grind and mix 3g of the above-obtained ball-milled petroleum coke with 9g of maleic anhydride, and then place it in a closed reactor for Diels-Alder reaction at a reaction temperature of 220℃ and a reaction time of 8h. After the reaction is completed, it is naturally cooled to room temperature, and the unreacted maleic anhydride is removed by washing with tetrahydrofuran, and dried at 50℃ in a vacuum oven for 12h to obtain a carboxylated petroleum coke precursor. Place 1g of carboxylated petroleum coke precursor in a tubular carbonization furnace, and in an argon atmosphere, heat it to 1400℃ at a heating rate of 3℃ / min, and keep it at this temperature for 2h, then cool it to 1000℃ at a cooling rate of 2℃ / min, and then cool it naturally to room temperature to obtain a hard carbon material.

[0060] Comparative Example 1

[0061] Take 1g of high-sulfur petroleum coke powder and place it in a tubular carbonization furnace. Under an argon atmosphere, heat it to 1500℃ at a heating rate of 3℃ / min and keep it at this temperature for 2h. Then cool it to 1000℃ at a cooling rate of 2℃ / min, and then naturally cool it to room temperature to obtain a soft carbon material. Fig.10 From the XRD diagram of the soft carbon material prepared in this comparative example, it can be seen that the material exhibits a highly graphitized structural feature, and the carbon layer spacing calculated according to the Bragg formula is 0.342 nm. Fig.11 This is the TEM image of the soft carbon material prepared in this comparative example. The material exhibits a long-range ordered structure with directional arrangement of carbon layers, and is mainly composed of graphite phase and graphite-like phase.

[0062] Comparative Example 2

[0063] 3g of high-sulfur petroleum coke powder was ball-milled at 800rpm for 1h to obtain ball-milled petroleum coke. 1g of ball-milled petroleum coke was placed in a tubular carbonization furnace, heated to 1500°C at a heating rate of 3°C / min under an argon atmosphere, and maintained at this temperature for 2h, then cooled to 1000°C at a cooling rate of 2°C / min, and then naturally cooled to room temperature to obtain a hard carbon material. Fig.13 From the XRD diagram of the hard carbon material prepared in this comparative example, it can be seen that ball milling will cause the petroleum coke-derived carbon structure to tend toward disordered development, and the carbon layer spacing calculated according to the Bragg formula is 0.353 nm.

[0064] Comparative Example 3

[0065] 3g of high-sulfur petroleum coke powder was placed in a tubular carbonization furnace, and heated to 260°C at a heating rate of 3°C / min in an oxygen atmosphere, and maintained at this temperature for 3h to obtain oxygen pre-oxidized petroleum coke. 1g of the above-obtained pre-oxidized petroleum coke was placed in a tubular carbonization furnace, and heated to 1500°C at a heating rate of 3°C / min in an argon atmosphere, and maintained at this temperature for 2h, and then cooled to 1000°C at a cooling rate of 2°C / min, and then naturally cooled to room temperature to obtain a soft carbon material.

[0066] Simulating battery assembly and testing

[0067] The carbon materials prepared in the above embodiments and comparative examples were respectively ground and mixed with SP and LA133+CMC binders in a mass ratio of 8:1:1, and an appropriate amount of pure water was added and placed in a glass bottle and stirred to form a uniformly dispersed slurry. The slurry was then coated on the current collector copper foil and vacuum dried at 100°C-12h. After drying, it was cut into discs with a diameter of 12mm. The average mass loading of the active material was 1.5mg.

[0068] The simulated battery was assembled in a glove box with Ar atmosphere, with sodium metal as the counter electrode, 1 mol / L NaPF6 (solvent including ethylene carbonate and dimethyl carbonate, volume ratio 1:1) as the electrolyte, glass fiber filter paper as the separator, and the electrode plates of the embodiment and the comparative example as the negative electrode to assemble into a CR2032 button battery. The battery was tested using Neware CT4008 (Shenzhen, China) at a constant temperature of 30°C and 20 mA g. -1 The constant current charge and discharge test was carried out under the current density, the discharge cut-off voltage was 0.01V, and the charge cut-off voltage was 3V. The test results are shown in Table 1. Figure 4-9 , Fig.12 ,and Figure 14-15 shown.

[0069] Table 1 Comparison of electrochemical properties of negative electrode materials prepared in Examples 1-6 and Comparative Examples 1-2

[0070]

[0071] analyze:

[0072] As can be seen from the above table, the method for preparing hard carbon materials proposed in the present invention has significant innovation and practicality. This method creatively changes the conventional path of directly carbonizing traditional soft carbon precursors to form highly graphitized soft carbon, and improves the crosslinking degree of the soft carbon precursor by introducing carboxyl induction, effectively inhibiting the rearrangement of graphite microcrystalline fragments inside the soft carbon precursor, and promoting the transformation from highly graphitized soft carbon to turbine-type structural hard carbon; the suitable carbon layer spacing and closed-pore structure inside the hard carbon provide a large number of effective storage sites for sodium ions. The surface of the hard carbon material is coated with a carbon shell, which effectively reduces the surface defects of the hard carbon material and significantly improves its initial coulombic efficiency, showing excellent reversible sodium storage specific capacity and initial coulombic efficiency, which greatly improves the application value of the soft carbon precursor.

[0073] It can be seen from Example 1 and Comparative Example 2, and Example 3 and Comparative Example 1 that by adding maleic anhydride to directionally graft carboxyl groups on the surface of petroleum coke, a highly cross-linked structure can be formed during the pyrolysis process, the graphitization process of the petroleum coke is delayed, the interlayer spacing is expanded and the closed-pore content is increased, and the surface of the hard carbon material is coated with a carbon shell, which effectively reduces the surface defects of the petroleum coke-based carbon material, thereby significantly improving the reversible specific capacity and initial coulombic efficiency of the petroleum coke-based carbon.

[0074] It can be seen from Examples 1-3 that appropriate ball milling treatment can destroy the microcrystalline structure and CC bonds of petroleum coke, increase the edge of the activated carbon layer, enhance the maleic anhydride modification effect, further expand the interlayer spacing and increase the closed-pore content, and enhance the reversible specific capacity and initial coulombic efficiency of petroleum coke-based carbon.

[0075] It can be seen from Examples 1 and 4 that increasing the amount of maleic anhydride increases the number of carboxyl groups grafted on the surface of petroleum coke, effectively preventing the rearrangement of the carbon layer, and realizing the transformation of the soft carbon precursor-derived carbon from highly graphitized soft carbon to turbine-type structured hard carbon, increasing the closed-pore content, and increasing the platform specific capacity.

[0076] It can be seen from Examples 1 and 5 that the method provided by the present invention has wide applicability to different carboxylic acid dienophiles. Acrylic acid can also undergo a Diels-Alder reaction with petroleum coke to achieve the grafting of surface carboxyl groups, achieving a modification effect similar to that of maleic anhydride, and obtaining a petroleum coke-based hard carbon material with excellent performance.

[0077] It can be seen from Examples 1 and 6 that lowering the high-temperature carbonization temperature will affect the closure of the pore structure formed in the low-temperature carbonization stage, resulting in an increase in the specific surface area of ​​the hard carbon material and a decrease in the closed pore volume, which in turn affects the initial Coulomb efficiency and platform specific capacity of the material. However, a lower carbonization temperature helps to retain more reversible sodium storage sites and maintain a lower degree of graphitization, so the slope specific capacity increases.

[0078] It can be seen from Example 3, Comparative Example 1 and Comparative Example 3 that due to the dense structure and surface inertness of petroleum coke, the conventional oxygen oxidation method cannot graft oxygen-containing functional groups such as carboxyl groups on the surface of petroleum coke, has limited effect on the structural regulation of petroleum coke-based carbon materials, and has little improvement in sodium storage performance.

[0079] The above detailed description of the present invention is intended to enable persons familiar with the technology in this field to understand the contents of the present invention and implement them. It does not limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a hard carbon material, characterized in that: The steps include: S1: uniformly mixing the soft carbon precursor powder and the carboxylic acid dienophile, and performing a Diels-Alder reaction in a reactor to obtain a carboxylated soft carbon precursor; S2 carbonizes the carboxylated soft carbon precursor at high temperature to obtain a hard carbon material.

2. The method for preparing a hard carbon material according to claim 1, characterized in that: The soft carbon precursor includes one or more of petroleum coke, asphalt and coal.

3. The method for preparing a hard carbon material according to claim 1, characterized in that: In step S1, before the soft carbon precursor powder and the carboxylic acid dienophile are uniformly mixed, the soft carbon precursor powder is also pre-treated by ball milling.

4. The method for preparing a hard carbon material according to claim 3, characterized in that: The ball milling speed is 400-1000 rpm, and the ball milling time is 0.1-4 h.

5. The method for preparing a hard carbon material according to claim 1, characterized in that: The carboxylic acid dienophile includes one or more of maleic acid, maleic anhydride, acrylic acid and acetylene dicarboxylic acid.

6. The method for preparing a hard carbon material according to claim 1, characterized in that: The mass ratio of the soft carbon precursor to the carboxylic acid dienophile is 1:(1-20).

7. The method for preparing a hard carbon material according to claim 1, characterized in that: The Diels-Alder reaction is carried out in a closed reactor at a temperature of 150-240° C. and a reaction time of 1-15 h.

8. The method for preparing a hard carbon material according to claim 1, characterized in that: Step S1 also includes washing and drying the carboxylated soft carbon precursor.

9. The method for preparing a hard carbon material according to claim 1, characterized in that: The temperature of the high-temperature carbonization is 800-1600° C., and the time of the high-temperature carbonization is 0.5-5 h.

10. Use of a hard carbon material obtained by the method according to any one of claims 1 to 9 in a sodium ion battery, characterized in that: The hard carbon material is used as the negative electrode of the sodium ion battery.

Citation Information

Patent Citations

  • Preparation method of sodium ion battery negative electrode carbon material with porous core-shell structure

    CN118083943A

  • Negative electrode material of sodium ion battery, preparation method of negative electrode material, negative electrode plate containing negative electrode material and sodium ion battery

    CN118289731A

  • Coal-based hard carbon negative electrode material of sodium ion battery and preparation method of coal-based hard carbon negative electrode material

    CN117894982A

  • Coal-based hard carbon negative electrode material for sodium-ion battery, preparation method of coal-based hard carbon negative electrode material and sodium-ion battery

    CN118183741A

  • Hard carbon negative electrode material and preparation method thereof, battery negative electrode plate and battery

    CN118754104A